2004
DOI: 10.1021/jf0350820
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography−Olfactometry and Chemical Quantitative Study of the Aroma of Six Premium Quality Spanish Aged Red Wines

Abstract: The aroma of six premium quality Spanish red wines has been studied by quantitative gas chromatography-olfactometry (GC-O) and techniques of quantitative chemical analysis. The GC-O study revealed the presence of 85 aromatic notes in which 78 odorants were identified, two of which-1-nonen-3-one (temptatively) and 2-acetylpyrazine-are reported in wine for the first time. Forty out of the 82 quantified odorants may be present at concentrations above their odor threshold. The components with the greatest capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
194
0
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(210 citation statements)
references
References 17 publications
9
194
0
7
Order By: Relevance
“…Q. humboldtii was also the oak with the highest concentration of this compound (Table 2). However, the concentration of this compound was below its perception threshold (40 µg/l, phenolic and smoky notes) (Culleré, Escudero, Cacho, & Ferreira, 2004) in all the wines.Furanic compounds had a similar extraction kinetic in all the wines in contact with oak chips, with the concentration of furfural, 5MF and 5HMF increasing considerably after 7 days' maceration, decreasing gradually during the oak maceration period and the Martínez-Gil, A. M., del Alamo-Sanza, M., Gutiérrez-Gamboa, G., . Volatile composition and sensory characteristics of Carménère wines macerating with Colombian (Quercus humboldtii) oak chips compared to wines macerated with American (Q. alba) and European (Q. petraea) oak chips.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…Q. humboldtii was also the oak with the highest concentration of this compound (Table 2). However, the concentration of this compound was below its perception threshold (40 µg/l, phenolic and smoky notes) (Culleré, Escudero, Cacho, & Ferreira, 2004) in all the wines.Furanic compounds had a similar extraction kinetic in all the wines in contact with oak chips, with the concentration of furfural, 5MF and 5HMF increasing considerably after 7 days' maceration, decreasing gradually during the oak maceration period and the Martínez-Gil, A. M., del Alamo-Sanza, M., Gutiérrez-Gamboa, G., . Volatile composition and sensory characteristics of Carménère wines macerating with Colombian (Quercus humboldtii) oak chips compared to wines macerated with American (Q. alba) and European (Q. petraea) oak chips.…”
mentioning
confidence: 71%
“…Probably because this wood, Romanian oak, was that with the highest concentration of this isomer (Table 2). However, in all wines the concentration of this isomer was lower than its perception threshold (790 µg/l) (Culleré et al, 2004), so that differences in the concentration of this isomer found in wines treated with the different oaks are probably not noticeable in their final aroma. Regarding the cis-β-methyl-γ-octalactone, as expected the wines macerated with American oak chips showed the highest concentration, as recorded by several authors (Rodríguez-Bencomo et al, 2008).…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Identification of hydrolyzed components was carried out by: (i) comparing the GC retention times and mass spectra, with those, when available, of the pure standard compounds, (ii) all mass spectra were also compared with the data system library (NIST, 2005 software, Mass Spectral Search Program V.2.0d; NIST 2005, Washington, DC), and (iii) retention index probes (RI) value were determined according to the van den Dool and Kratz [33]. For the RI determination, a C 8 -C 20 n-alkanes series were used, and these values were compared, when available, with values reported in the literature for a BP-20 and similar chromatographic columns [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52].…”
Section: Gc-qms Conditionsmentioning
confidence: 99%